Pengaruh Aspek Tangibles, Responsiveness, Assurance dan Emphaty dalam Pelayanan Perbaikan Terhadap Kepuasan Pelanggan di Kantor Pusat Perusahaan Daerah Air Minum (Pdam) Kabupaten Karanganyar - Fajar Wahyu Karyadi; Kim Budiwinarto; R Rohwiyati; Roch Mulyani; Astrid Widayani (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2018)
In this research has the objective to determine the effect tangible aspects, responsiveness, assurance and empathy in service improvements to customer satisfaction in the Perusahaan Daerah Air Minum (PDAM) Karanganyar either partially or simultaneously. The hypothesis in this study are: Suspected tangible aspects, responsiveness, assurance and empathy in service improvements significant effect on customer satisfaction in the Perusahaan Daerah Air Minum (PDAM) Karanganyar either partially or simultaneously. Necessary data in this study are primary data obtained by questionnaire from a sample of 52 respondents. Analysis of the data used in this research is multiple linear regression,t test, F test and coefficient of determination. The results of data analysis in this study can be concluded that the tangible aspects, responsiveness, assurance and empathy in service improvements significant effect on customer satisfaction in the Perusahaan Daerah Air Minum (PDAM) Karanganyar either partially or simultaneously.